Molecular characterization of a hepcidin homologue in starry flounder (Platichthys stellatus) and its synergistic interaction with antibiotics. Issue 83 (December 2018) - Liu, Zi-Ming; Chen, Jie; Lv, Yao-Ping; Hu, Ze-Hui; Dai, Qing-Min; Fan, Xiao-Li
Abstract: Hepcidins are small cysteine-rich antimicrobial peptides that play an important role in host immunity against pathogenic organisms. Most fish hepcidins exert bactericidal activities against a wide range of pathogens. In this study, we identified a cDNA sequence encoding a hepcidin homologue (PsHepcidin) in the starry flounder Platichthys stellatus . The predicted amino acid sequence of PsHepcidin comprises a signal peptide and a prodomain, which are followed by the mature peptide. Sequence analysis revealed that PsHepcidin belongs to the fish HAMP2 cluster and that it is closely related to mudskipper hepcidin-2. Expression of PsHepcidin mRNA was detected in all examined immune-related tissues, with the highest transcript levels being found in the liver. In response to lipopolysaccharide treatment, PsHepcidin was significantly up-regulated in the liver, kidney, and spleen in a time-dependent manner. Chemically synthesized mature peptides of PsHepcidin were found to exhibit broad antimicrobial activity in vitro . We also investigated the combined effect of PsHepcidin and conventional antibiotics and found that these combinations showed synergistic effects against most of the examined bacterial strains. Collectively, the results of this study indicate that PsHepcidin exhibits potent antibacterial activity both independently and when used in combination with conventional antibiotics. Highlights: We cloned a hepcidin gene (PsHepcidin) from the flounder Platichthys stellatus. PsHepcidin may play a singular role in immune responses against various pathogens. PsHepcidin showed antibacterial activity against selected bacterial pathogens. In vitro, PsHepcidin showed synergistic activity in combination with antibiotics.